The relationship between sports communication strategies and sports image creation with sports communication performance in Thailand - Ritnuang, Jutarat (Edelweiss Applied Science and Technology, 2024)
This research aimed to develop a model of the relationship between sports communication strategies and sports image building with sports communication performance in Thailand. This research was mixed-methods research between quantitative and qualitative research, quantitative methodology was used to test the cause-and-effect relationship between sports communication strategies and sports image factors with sports communication performance in Thailand. Data were collected using questionnaires with 151 mass media organizations that conduct sports communication activities in Thailand. And qualitative methodology was conducted using phenomenological methods from in-depth interviews and the results of in-depth interviews were confirmed by holding focus groups with 3 members of the Thai Journalists Association who supervise sports mass media members and 2 sports communication scholars. Data was analyzed using confirmatory factor analysis and structural equation modeling. The results of research hypotheses founded that 1) sports communication strategies have a direct effect on the sports communication performance in Thailand and have an indirect effect on the sports communication performance in Thailand through sports image creation, 2) sports communication strategies have a direct effect on sports image creation, and 3) sports image creation has a direct effect on sports communication performance in Thailand. The analysis founded that the hypothesized model was consistent with the empirical data and passed the criteria with a χ2 value of 13.78, p-value of 0.79, χ2/df value of 0.72, GFI value of 0.98, AGFI value of 0.95, and RMSEA value of 0.00. The benefits of this research can explain the causal relationship between sports communication strategies and sports image creation and the effectiveness of sports communication in Thailand. The results of the study can be used to manage sports communication in Thailand, leading to sustainable performance for the sports industry.